Design and Build a Water Pump Protection Tool Using IOT (Internet Of Things) Based Water Flow Sensor - Muhammad Faishol; Munaf Ismail; Jenny Putri Hapsari (Journal of Applied Science and Technology, 2022)
Water is often taken with the help of a pump to remove water from the well to be filled into the reservoir.However, often during the dry season, many pumping machines are damaged because the pump is on but thewater in the well (source) is empty and no one knows it, so the pump engine does not turn off, therefore it cancause the pump to fail. be damaged. This study designed a system that can monitor the flow of water using theBlynk application. Monitoring is carried out using a smartphone with a NodeMCU ESP8266 microcontrollerconnected to the internet network. The sensor used is a water flow sensor to detect the flow of water. The Blynkapplication is used by the user as a data display for the NodeMCU ESP8266 microcontroller which is integratedinto the internet network. The results of the research water flow sensor has worked well on the water pump.After testing the distance, the distance is detected indefinitely provided that the microcontroller and the blynkapplication are connected to the internet network, and do not experience internet network trouble.